Customer Engagement and Decision to Watch Indonesian Films in Cinemas: A Relationship Marketing Perspective - Muhammad Fadheel Djamaly,; Djumarno,; Rina Astini,; Daru Asih, (Communication Today, 2025)
Customer engagement reflects the intensity of interaction between customers and products in the market. In the film industry, customers who enjoyed watching movies in cinemas tend to have more intensive interactions with upcoming films. This study analysed the mediating role of customer engagement in the influence of the lead actor, film genre, film ratings, and online reviews on the decision to watch Indonesian films in cinemas. The research employed a quantitative approach with a survey of 315 respondents. Data was analysed by using Structural Equation Modelling through Smart PLS software. The lead actor, film genre, movie ratings, and online reviews positively and significantly influenced customer engagement with films. Customer engagement, in turn, positively and significantly influenced the decision to visit a cinema to watch Indonesian films. Customer engagement is proven to be an appropriate mediator between the four independent variables and the decision to watch Indonesian films in cinemas. Incorporating customer engagement as a mediator in the relationship between the lead actor, film genre, film ratings, online reviews is therefore important. These research findings enrich relationship marketing theory by emphasising the importance of customer engagement in strengthening long-term relationships and consumer behaviour theory by enhancing customer loyalty.